Hidayani PERAN GURU DALAM PEMBERIAN LAYANAN BIMBINGAN KONSELING KE PESERTA DIDIK DI SEKOLAH SD NEGERI 35 KOTA SORONG: PERAN GURU DALAM PEMBERIAN LAYANAN BIMBINGAN KONSELING KE PESERTA DIDIK DI SEKOLAH SD NEGERI 35 KOTA SORONG - Hidayani, Hidayani; Mahendra, Faisal Eka; Sijabat, Jenro; Sundari, Sundari; Soleha, Almar Atu; Ahmad, Rizky Ekawaty (Sangkalemo : The Elementary School Teacher Education Journal, 2024)
This study was conducted at SD Negeri 35 Kota Sorong to explore the role of teachers in providing counseling services to students. The methods used in this study were observation, interviews, and documentation to obtain data on the effectiveness of counseling services in enhancing students' learning independence. The results showed that counseling services are highly beneficial in helping students understand themselves, overcome problems they face, and develop learning independence. Teachers play a crucial role in identifying students who need assistance, providing solutions to the problems faced by students, and organizing strategies to handle specific cases such as bullying, family issues, or learning difficulties. The main challenge faced is the distance between students' homes and the school, causing tardiness. The proposed solution is to follow school zoning regulations to minimize this issue. Counseling services are routinely provided every Saturday, with the formation of special teams responsible for addressing various student problems. The school's good strategy and structure have successfully minimized problems, making parents satisfied with the services provided. This study confirms that structured and consistent counseling services by teachers can help students overcome various issues and improve the quality of education in schools.